Hypnotic and muscle relaxant activity of thymoquinone, the major active constituent of Nigella sativa seeds, and its effects on locomotor activity and motor coordination in mice - S Parvardeh; H Hosseinzadeh (Institue of Medicinal Plants, ACECR, 2003)
We have previously shown that thymoquinone, the major active constituent of Nigella sativa seeds, exhibited anticonvulsant effect in pentylenetetrazole model. In the present study, in order to clarify the other actions of thymoquinone on the CNS, we investigated its hypnotic and muscle relaxant effects using pentobarbital-induced hypnosis and the traction test, respectively. Also, we evaluated the effects of thymoquinone on locomotor activity and motor coordination using the open-field activity and the rotarod tests, respectively. The results showed that thymoquinone did not show any hypnotic effect but exerted muscle relaxation in 30% of mice treated with the dose of 80 mg/Kg i.p. In rotarod test, thymoquinone (40 and 80 mg/Kg, i.p.) produced motor incoordination dose dependently. In open-field test, we found that thymoquinone with lower doses (1 and 2 mg/Kg, i.p.) could suppress locomotor activity and locomotor-associated behaviors. These findings indicate that thymoquinone has not any hypnotic effect, but produces muscle relaxation, as well as motor incoordination, and reduces the locomotor activity.